2012
DOI: 10.1021/jf304036c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nano/Submicrometer Yam and Its Benefits on Collagen Secretion from Skin Fibroblast Cells

Abstract: Nano/submicrometer-scaled yam particles have been prepared by using media-milling. The particle size of media-milled yam was confirmed by the laser light scattering method and scanning electron microscopy. Influences of media-milled yam on skin fibroblast cells (WS1) were evaluated. The size reduction did not significantly alter the proximate composition, and the presence of nanoparticles was not toxic to WS1 cells. The contents of bioactive compounds (diosgenin, stigmasterol, and β-sitosterol) were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The gradual increase of anthocyanin extractability in the media milled red rice could be attributed to the complete breakdown of the material matrix, which enhanced the efficiency during solvent extraction. The enhanced extraction of the bioactive compounds after the media-milling process has also been reported in another study . Previous studies have proved that the prominent anthocyanins in colored rice are cyanidin-3-glucoside and peonidin-3-glucoside.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The gradual increase of anthocyanin extractability in the media milled red rice could be attributed to the complete breakdown of the material matrix, which enhanced the efficiency during solvent extraction. The enhanced extraction of the bioactive compounds after the media-milling process has also been reported in another study . Previous studies have proved that the prominent anthocyanins in colored rice are cyanidin-3-glucoside and peonidin-3-glucoside.…”
Section: Resultssupporting
confidence: 57%
“…Since the original red rice is a mixture of starch, protein, and dietary fiber, it is highly possible that media-milling can be effective in producing nano/submicrometer particles from other resources containing either one or more components. And some studies have already confirmed the production of nano/submicrometer particles from soy bean, yam, and Ganoderma tsugae. ,, …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As a phytochemical is known to present anti-inflammatory action and also in the control of dyslipidemias (RAJU; MEHTA, 2009). It has antioxidant properties and stimulates the production of collagen (RAJU; MEHTA, 2009;CHIANG et al, 2012), which are increasingly important in the pharmaceutical and cosmetic industries.…”
Section: Introductionmentioning
confidence: 99%